ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN SEMBAKO DI GROSIR CV BERDIKARI KABUPATEN MIMIKA - Risna Jend; Tri Apriyono (BORJUIS: JURNAL OF ECONOMY, 2024)
This study aims to determine what factors influence the sale of basic necessities at the CV Berdikari wholesaler in Mimika Regency. The hypothesis test of this study states that it is suspected that price, personal selling, and distribution factors have a positive and significant eflect on the sale of basic necessities at the CV Berdikari wholesaler. This study uses a descriptive method. Data collection using a questionnaire with a population used in the study consisting of 80 CV Berdikari wholesale customers. The data analysis technique uses the Partial Last Squeezer (PLS) analysis method on the Smart PLS 4 application. The measurement results show that price and personal selling factors have a positive and insignificant eflect on sales. Meanwhile, the distribution factor has a positive and significant eflect on the sale of basic necessities at the CV Berdikari wholesaler in Mimika Regency.